Bio-inspired fluorescence color-tunable soft actuators with a self-healing and reconfigurable nature. (June 2022) - Meng, H.; Yang, X.; Wang, Y.; Wang, C.; Ye, W.; Ma, F.; Han, T.; Qi, J.; Wang, C.
Abstract: The adaptive behaviors of organisms in response to different environments can inspire the development of smart materials. These biomimetic color-changing actuating materials (BCCAMs) with complex shape memory (SM), self-healing, shape reconfigurable and reprocessing properties may be exactly what the flexible actuators/robots/electronic skins need. Here, we prepared an ultra-high strain (∼1600%) soft actuation material with fluorescence changes, self-healing, and SM performance under a single stimulus by a simple method. At the same time, we developed a simple strategy based on welding to achieve actuators that have a reconfiguring three-dimensional (3D) deformation and medium temperature reprocessing. The resulting 3D soft actuators can achieve effective coordination of these functions. Flexible actuators with multiple functions that can be triggered by a single switch are expected to have value in soft robots, flexible electronic skins, and so on. Highlights: An ultra-high strain (∼1600%) soft actuation material with multiple functions under a single stimulus. A strategy based on welding to achieve actuators with 3D shape reconfigurability and medium temperature reprocessing. The flexible actuators with multiple functions are expected to have value in 3D printing and soft robots.